2018
DOI: 10.1096/fj.201701242rr
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 induces cellular stress microenvironment of melanocytes to promote autophagic cell apoptosis in vitiligo

Abstract: Vitiligo is a depigmentary disorder that develops as a result of the progressive disappearance of epidermal melanocytes. Stress can precipitate or exacerbate a skin disease through psychosomatic mechanisms. Stress exposure induces vitiligo-like symptoms in mice, as cellular damage to melanocytes causes synthetic pigment loss. Stress also increases IL-17, IL-1β, and antimelanocyte IgG in model mouse serum. Up-regulation of the IL-1β transcript in patients suggests its possible role in autoimmune pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 48 publications
1
60
0
Order By: Relevance
“…Therefore, we concluded that the Th17 cell-related cytokines environment modulated by downregulation or upregulation of mGluR4 in BMDC affected the expression of MITF and its downstream genes, along with the morphology and melanin production in B16 cells, leading to the local pigment abnormity. Recently Zhou et al (36) found that IL-17 promoted the autophagymediated apoptotic process, which contributed to the pathology of vitiligo. In a future study, it is suggested to probe into whether the conditioned media for CD4 coculture experiment would impact cell cytotoxicity, cell cycle, etc., of B16 cells, to determine how the Th17 cytokines would destroy B16 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concluded that the Th17 cell-related cytokines environment modulated by downregulation or upregulation of mGluR4 in BMDC affected the expression of MITF and its downstream genes, along with the morphology and melanin production in B16 cells, leading to the local pigment abnormity. Recently Zhou et al (36) found that IL-17 promoted the autophagymediated apoptotic process, which contributed to the pathology of vitiligo. In a future study, it is suggested to probe into whether the conditioned media for CD4 coculture experiment would impact cell cytotoxicity, cell cycle, etc., of B16 cells, to determine how the Th17 cytokines would destroy B16 cells.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ There have also been many reports confirming elevated levels of circulating IL-17 and increased numbers of Th17 lymphocytes in patients with non-segmental vitiligo [33][34][35] . Furthermore, IL-17 has been reported to damage melanocytes 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Skin epidermis, a self‐regenerating organ, constantly sheds and replaces damaged and worn‐out skin cells (Orioli & Dellambra, ; Yang & Kang, ; Zhang et al, ). Although mitochondrial dysfunction adversely affects primarily nonregenerative tissue, the neuromuscular system, and internal organs, cells in every tissue type, including skin, require a continuous and adequate supply of mitochondrial energy for their survival and proper function (Baeeri et al, ; Dinkova‐Kostova, Kostov, & Kazantsev, ; Joshi & Mochly‐Rosen, ; Martinelli et al, ; Naidoo, Hanna, & Birch‐Machin, ; Wlaschek, Singh, Sindrilaru, Crisan, & Scharffetter‐Kochanek, ; Zhou et al, ). Representing the outermost surface of the body, skin is uniquely vulnerable to a plethora of environmental insults.…”
Section: Nrf2‐activating Therapeuticsmentioning
confidence: 99%
“…muscular system, and internal organs, cells in every tissue type, including skin, require a continuous and adequate supply of mitochondrial energy for their survival and proper function(Baeeri et al, 2019;Dinkova-Kostova, Kostov, & Kazantsev, 2018;Joshi & Mochly-Rosen, 2018;Martinelli et al, 2017;Naidoo, Hanna, & Birch-Machin, 2018; Wlaschek, Singh, Sindrilaru, Crisan, & Scharffetter-Kochanek, 2019;Zhou et al, 2018). Representing the outermost surface of the body, skin is uniquely vulnerable to a plethora of environmental insults.Exposure to harmful chemicals, xenobiotics, oxidative stress, and solar UV-radiation is mitigated by various protective mechanisms that rely on signaling networks and the expression of proteins involved in the detoxification of compounds or reactive oxygen speciesDodson et al, 2019;Hiebert et al, 2018;Jadkauskaite et al, 2017;Raghunath et al, 2018;Siegenthaler et al, 2018;Sivandzade, Prasad, Bhalerao, & Cucullo, 2019;Tonelli, Chio, & Tuveson, 2018;Vega, Krajisnik, Zhang, & Wondrak, 2017;Yamamoto, Kensler, & Motohashi, 2018).…”
mentioning
confidence: 99%